2017
DOI: 10.1111/jep.12685
|View full text |Cite
|
Sign up to set email alerts
|

Surgical glue in laparoscopic sleeve gastrectomy: An initial experience and cost‐effectiveness analysis

Abstract: Surgical glue might be a safe and cost-effective intervention in laparoscopic sleeve gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Bleeding control methods commonly aimed to control hemorrhage in the extra luminal origin staple line, clipping, fibrin sealant application or monopolar cautery like us. Mercier et al [5] compared effect of surgical glue with no staple line reinforcement method group and they find no differentiation on bleeding and leak rates. Coskun et al [1] reported that fibrin glue application on staple line, is an extraluminal bleeding control technique, zero leak and 0.3 % bleeding rate.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding control methods commonly aimed to control hemorrhage in the extra luminal origin staple line, clipping, fibrin sealant application or monopolar cautery like us. Mercier et al [5] compared effect of surgical glue with no staple line reinforcement method group and they find no differentiation on bleeding and leak rates. Coskun et al [1] reported that fibrin glue application on staple line, is an extraluminal bleeding control technique, zero leak and 0.3 % bleeding rate.…”
Section: Discussionmentioning
confidence: 99%
“…Use of glue to reinforce the staple line has not been shown to reduce postoperative hemorrhage. 39 The use of tranexamic acid as a routine intraoperative method of reducing hemorrhage has been proposed. 40 …”
Section: Discussionmentioning
confidence: 99%